Effects of Unsaturated Flow on Hydraulic Head Response to Earth Tides–An Analytical Model. Issue 2 (8th February 2022) - Liang, Xiuyu; Wang, Chi‐Yuen; Ma, Enze; Zhang, You‐Kuan
Abstract: Responses of groundwater levels to Earth tides have been widely studied to evaluate aquifer properties because it has been shown to be an economical and effective approach to estimate aquifer parameters. Existing studies suggest that unsaturated zones may have non‐negligible effects on groundwater responses to Earth tides in an unconfined aquifer. However, an analytical model for these effects is unavailable; as a result, the impacts of the unsaturated flow on the tidal response of water levels has not been fully explored. Here we present an analytical solution for the coupled unsaturated‐saturated flow equation, which is linearized by the perturbation method, to study the hydraulic head responses to Earth tides. The solutions are compared with that from numerical simulation using the finite‐element method built in COMSOL Multiphysics and an existing numerical model. The results indicate that the unsaturated zone has significant impacts on the hydraulic head responses to Earth tides. The traditional model for an unconfined aquifer that neglects the effects of an unsaturated zone commonly underestimates the amplitude ratio and overestimates the phase shift. The fluctuations of the water table near the ground surface (<1.0 m) causes dramatic variations of both amplitude ratio and phase shift, which in turn cause the traditional model to fail in estimating aquifer parameters. The solutions are applied to field data to interpret large seasonal variations in the tidal responses. The solutions derived in this study should be an important addition to existing analytical models for tidal analysis. Key Points: An analytical model for hydraulic head response to earth tides considering effects of unsaturated zones was developed The models that neglect the effects of unsaturated zones underestimate amplitude ratio and overestimate phase shift Fluctuating water table causes changes in the amplitude ratio and phase shift, which are important to consider in estimating parameters